Technology and innovation in enhancing primary health care: The role of digital solutions in strengthening healthcare systems - Vervloet , Thaís Silva; Ribeiro, Felipe Silva; Batista, Paulo Henrique Mariano; Vesco, Jessica Ribeiro Dal (Seven Editora, 2023)
Introduction: The implementation of digital solutions in primary health care has brought significant changes and improvements to traditional systems. However, the integration between traditional medical cultures and digital solutions remains a hurdle to be overcome. Despite this, the implementation of these solutions brings advantages such as improved access to care, increased patient engagement, enhanced efficiency, and better health outcomes. However, there are challenges to be overcome, such as resistance to change, concerns about privacy and data security, as well as infrastructure and internet access issues. Through collaboration between healthcare providers, policymakers, and technology developers, it is possible to successfully overcome these challenges and integrate digital solutions into primary health care. Methodology: An integrative literature review was conducted to analyze case studies and relevant research on the implementation of digital solutions in primary health care. Articles published between 2010 and 2023 were selected from databases such as PubMed, Scielo, and Medline, addressing the benefits, challenges, and outcomes related to digital solutions. Data analysis was performed qualitatively and quantitatively, grouping relevant information and highlighting improvements in primary health care. Objective: This scientific article aims to explore the impact of digital solutions in primary health care, comparing and contrasting traditional systems with the advantages and challenges of implementing digital solutions. Discussion: The implementation of digital solutions in primary health care has brought significant advantages, such as improved access to care, increased efficiency, and better health outcomes. However, it also presents challenges, including resistance to change, concerns about data privacy, and the need to assess cost-effectiveness. Case studies highlight both successful and unsuccessful implementations, providing valuable insights into the factors that contribute to success or failure. To harness the full potential of digital solutions in primary health care, it is crucial to consider the impact on the doctor-patient relationship, ensure effective data management and analysis, and integrate digital solutions into existing healthcare systems. Additionally, ethical considerations, adequate training for healthcare professionals, and patient acceptance play important roles in the successful implementation of these solutions. Conclusion: The implementation of digital solutions in primary health care brings various advantages, such as improved access, increased efficiency, and better health outcomes. However, it is essential to address ethical issues, such as data privacy and security, and ensure that these solutions are accepted, effective, and integrated into existing healthcare systems. Training and education for healthcare professionals play a crucial role in the successful adoption of these solutions, as well as patient acceptance and adoption. Looking to the future, advances in digital technology have great potential to transform primary health care, provided the necessary skills are considered and there is collaboration among stakeholders. By addressing these considerations, primary health care can make the most of the benefits of digital solutions, improving healthcare delivery for individuals. DOI:https://doi.org/10.56238/globalhealthprespesc-022